Academic springboard: The chief resident position correlates with career path in emergency medicine. Issue 4 (15th August 2021) - Jordan, Jaime; Hopson, Laura R.; Clarke, Samuel O.; Frisch, Adam; Chipman, Anne K.; Curato, Mark; Janicki, Adam; Calles, Ignacio; Ilgen, Jonathan; Gottlieb, Michael
Abstract: Background: The chief resident role often includes additional administrative and educational experiences beyond those of nonchief senior residents. It is unclear to what extent these experiences influence the postresidency career path of those selected as chief residents. The objective of this study was to evaluate the association of chief resident status on immediate postresidency career characteristics relative to nonchief residents in emergency medicine (EM). Methods: We retrospectively analyzed graduate data from 2016 to 2020 at six accredited EM residency programs. Participating sites were geographically diverse and included 3‐ and 4‐year training formats. Each site abstracted data using a standardized form including program, year of graduation, chief resident status, publications during residency, and immediate postresidency position (academic vs. nonacademic). We calculated descriptive statistics and performed logistic regression to explore differences between the chief resident cohort and other graduates. Results: We gathered information on 365 total graduates (45.8% from 3‐year programs and 54.2% from 4‐year programs) including 93 (25.5%) chief residents. A total of 129 (35%) graduates assumed an academic position immediately following residency. Fifty‐six (60%) of 93 chief residents assumed an academic position immediately following residency, compared to 74 (27%) of 272 other graduates. After program, year of graduation, and number of publications completed during residency were controlled for, chief resident status was a significant predictor of immediate postresidency academic career (odds ratio for a chief resident assuming an academic job = 5.36, 95% confidence interval = 3.10 to 9.27). Conclusion: The chief resident role within EM is significantly associated with pursuit of an academic position immediately following residency compared to nonchiefs.